A cross-sectional study for the mental health status and sleep quality among college students in Macao during the COVID-19 pandemic - Tao, Xiaoyu; Chen, Dong; Fan, Yawen; Zhang, Lanxin; Shan, Houqian; Wei, Yi; Yu, Xi; Zhong, Tian; Wang, Ling; Chung, Sookja Kim; Yu, Yaqin; Xiao, Ying (PeerJ, 2021)
Objectives The main focus of this study was to investigate the effect of the coronavirus disease (COVID-19) pandemic on the mental health condition and sleep quality of college students in Macao. In addition, the students’ behaviours during the pandemic, such as drinking alcohol, taking sleeping pills, and seeking psychological counselling were analyzed. Method A cross-sectional survey of mental health and sleep quality status, as well as the possible behavioral risk factors, was conducted among the college students of Macao in August, 2020 during the COVID-19 pandemic. An online self-report questionnaire survey method was applied to assess the general demographics and related lifestyle behaviors of students. The general mental health condition and sleep quality were evaluated through the General Health Questionnaire (GHQ-12) and Pittsburgh Sleep Quality Index (PSQI) questionnaires, respectively. The main statistical methods included the Chi-square test, Bonferroni correction, and Pearson correlation. Data analysis was performed using SPSS Version 24.0. Results A total of 980 students were investigated in the study, of which 977 completed the survey. During the COVID-19 pandemic period, overall college students in Macao were psychologically well adjusted and reported good quality of sleep. However, female students were in poorer psychological condition than males (P < 0.05). Moreover, the students over 20 years of age had poorer sleep quality than students aged less than or equal to 20 (P < 0.05). The significant differences were found among the students in different study majors for the mental health status and sleep quality (both P < 0.05), which were associated with certain behaviors, such as drinking alcohol, taking sleeping pills, and seeking for help in psychological counselling during the COVID-19 pandemic period. Conclusions Poor mental health status could be either the consequence or cause of sleep disturbance, which might further affected physical health. Therefore, regular assessment of mental health condition and sleep quality of college students is particularly necessary during public health emergencies, such as the COVID-19 pandemic, and appropriate intervention should be provided to the students.
Keywords: Mental health status; Sleep quality; College students; COVID-19